An underappreciated DIET for anaerobic petroleum hydrocarbon‐degrading microbial communities. Issue 1 (30th August 2020) - Aulenta, Federico; Tucci, Matteo; Cruz Viggi, Carolina; Dolfing, Jan; Head, Ian M.; Rotaru, Amelia‐Elena
Abstract : Direct interspecies electron transfer (DIET) via electrically conductive minerals can play a role in the anaerobic oxidation of petroleum hydrocarbons in contaminated sites and can be exploited for the development of new, more effective bioremediation approaches.